2020
DOI: 10.1044/2020_jslhr-19-00228
|View full text |Cite
|
Sign up to set email alerts
|

Communication Modes and Functions in Children With Cerebral Palsy

Abstract: Purpose This study seeks to determine how speech-language impairments relate to the frequency and diversity of communication modes and functions produced by children with cerebral palsy (CP) during interactions with their mothers. Method We studied 40 children with CP ( M age = 62 months) comprising three groups: those who were unable to speak and had anarthria ( n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Our understanding of communication impairment associated with CP has, therefore, been based primarily on profiles of children ≥2 years of age. 5,8,9,28,29 One reason for the lack of data for <2 years of age is that historically CP has been diagnosed between 12 and 24 months of age. 30 However, in 2017, international clinical practice guidelines 31,32 have enabled accurate early identification of CP before 6 months, and as early as 3 months corrected age, using a combination of standardized measures of early motor ability with predictive capabilities, such as the General Movement Assessment, 33 and clinical reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of communication impairment associated with CP has, therefore, been based primarily on profiles of children ≥2 years of age. 5,8,9,28,29 One reason for the lack of data for <2 years of age is that historically CP has been diagnosed between 12 and 24 months of age. 30 However, in 2017, international clinical practice guidelines 31,32 have enabled accurate early identification of CP before 6 months, and as early as 3 months corrected age, using a combination of standardized measures of early motor ability with predictive capabilities, such as the General Movement Assessment, 33 and clinical reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, there was a high level of practice in capturing verbal and nonverbal child complaints. There is a possibility that nonverbal communication is carried out in daily care in the field of pediatric nursing, such as care for children in the process of language development 17 and care for severely retarded children who have difficulty expressing linguistically 18,19 . This study showed that the level of practice for physical pain was high, but simultaneously, it became clear that the ratio of using an assessment scale tailored to the specific child was low.…”
Section: Discussionmentioning
confidence: 79%
“…There is a possibility that nonverbal communication is carried out in daily care in the field of pediatric nursing, such as care for children in the process of language development 17 and care for severely retarded children who have difficulty expressing linguistically. 18,19 This study showed that the level of practice for physical pain was high, but simultaneously, it became clear that the ratio of using an assessment scale tailored to the specific child was low. It may be necessary to strengthen education using ELNEC-JPPC to appropriately assess the symptoms of individual children.…”
Section: Nursing Practices Of Ppc In Japanmentioning
confidence: 96%